1992
DOI: 10.1093/nar/20.12.3199
|View full text |Cite
|
Sign up to set email alerts
|

Gene clusters for ribosomal proteins in the mitochondrial genome of a liverwort,Marchantia polymorpha

Abstract: We detected 16 genes for ribosomal proteins in the complete sequence of the mitochondrial DNA from a liverwort, Marchantia polymorpha. The genes formed two major clusters, rps12-rps7 and rps10-rpl2-rps19-rps3-rpl16-rpl5- rps14-rps8- rpl6-rps13-rps11-rps1, very similar in organization to Escherichia coli ribosomal protein operons (str and S10-spc-alpha operons, respectively). In contrast, rps2 and rps4 genes were located separately in the liverwort mitochondrial genome (the latter was part of the alpha operon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…While this extension sequence might contain the mitochondrial targeting information for the yeast mitochondrial protein, there is no apparent need for such a targeting sequence in a polypeptide translated within maize mitochondria. Indeed, it has been argued that translation of L16 in the plant mitochondria initiates at a GUG valine codon (31,32). For example, the amino-terminal residue of the liverwort (Marchantia polymorpha) sequence shown in Figure 4 is assumed to be a methionine encoded by a GUG initiation codon because there are no suitable candidate AUG initiation codons (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this extension sequence might contain the mitochondrial targeting information for the yeast mitochondrial protein, there is no apparent need for such a targeting sequence in a polypeptide translated within maize mitochondria. Indeed, it has been argued that translation of L16 in the plant mitochondria initiates at a GUG valine codon (31,32). For example, the amino-terminal residue of the liverwort (Marchantia polymorpha) sequence shown in Figure 4 is assumed to be a methionine encoded by a GUG initiation codon because there are no suitable candidate AUG initiation codons (31).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been argued that translation of L16 in the plant mitochondria initiates at a GUG valine codon (31,32). For example, the amino-terminal residue of the liverwort (Marchantia polymorpha) sequence shown in Figure 4 is assumed to be a methionine encoded by a GUG initiation codon because there are no suitable candidate AUG initiation codons (31). If L16 translation in maize and Petunia initiates at the identical GUG valine codon instead of at an upstream AUG, then these proteins would also lack N-terminal extensions and their N-termini would align with that of E.coli L16.…”
Section: Resultsmentioning
confidence: 99%
“…One ribosomal protein gene (varl) is present on the yeast mitochondrial genome [3], while the rest of the expected 60-80 proteins is encoded in the nucleus and imported from the cytosol into the organelle (for review see [4]). In Marchantiapolymorpha sixteen genes coding for ribosomal proteins have been identified on the mitochondrial genome from homology to their bacterial counterparts [5]. The organization of ribosomal protein genes in the liverwort is similar to the situation found in E. coli [6] but differs in higher plants where the genes are scattered far apart in the genome [7].…”
Section: Introductionmentioning
confidence: 89%
“…Ten independant cDNA clones were found that were polyadenylated and showed high similarity to the mitochondrial rpslO sequences of potato [10], pea [9], and Marchantia [5]. [5], Pisum sativum (P. sativum) [9], and Solanum tuberosum (S. tubersosum) [10], the cyanellar sequence of Cyanophora paradoxa (C. paradoxa) [24], the cyanobacterial sequence of Spirulina platensis (S. platensis) [25], and the eubacterial sequence of Escherichia coil (E. coli) [26] are shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation